The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11010-007-9557-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of advanced glycation end product (AGE) receptors and apoptosis by AGEs in osteoblast-like cells

Abstract: Advanced glycation end products (AGEs) have been proposed as the pathological mechanisms underlying diabetic chronic complications. They may also play a role in the pathogenesis of diabetic osteopenia, although their mechanisms of action remain unclear. We investigated the protein (immunofluorescence) and gene expression (realtime RT-PCR) of two receptors for AGEs, RAGE and galectin-3, as well as their regulation by AGEs, and the apoptotic effect on osteoblast-like cells (UMR106 and MC3T3E1) in culture. AGEs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 24 publications
4
64
0
5
Order By: Relevance
“…In the nucleus, STAT3 binds to target genes and induces the transcription of several genes associated with cell proliferation and anti-apoptosis [48, 49]. We have been working on the gene regulation and functional characterization of galectin-3 over the years [16, 31, 46, 5456]. Several studies suggest that galectin-3 is involved in tumor cell adhesion, proliferation, angiogenesis, cancer progression and metastasis [13, 1620].…”
Section: Discussionmentioning
confidence: 99%
“…In the nucleus, STAT3 binds to target genes and induces the transcription of several genes associated with cell proliferation and anti-apoptosis [48, 49]. We have been working on the gene regulation and functional characterization of galectin-3 over the years [16, 31, 46, 5456]. Several studies suggest that galectin-3 is involved in tumor cell adhesion, proliferation, angiogenesis, cancer progression and metastasis [13, 1620].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, non-cross-linking types of AGEs, such as carboxymethyllysine, deteriorate osteoblastic function [86,87] via interaction with the cell surface receptor of AGEs, receptor for advanced glycosylation end products (RAGE) [88]. Such adverse effects of AGEs on osteoblastic function are also reported by Pen itself [89].…”
Section: Lysyl Oxidase and Total Enzymatic Cross-link Formationmentioning
confidence: 99%
“…AGEs have a physiological function and act through their receptors. It has been shown that receptor for AGEs (RAGE) is expressed in osteoblasts and osteocytes [25,26], and hyperglycemia increased the expression of RAGE [27]. We previously demonstrated that combination of high glucose and AGEs inhibited the mineralization of osteoblastic MC3T3-E1 cells [27], and that AGEs inhibited the osteoblastic differentiation or mineralization of mouse stromal ST2 cells and human mesenchymal stem cells by decreasing osterix expression, increasing transforming growth factor (TGF)-β expression, and suppressing endoplasmic reticulum stress proteins [28][29][30] (Fig.…”
Section: Dysfunction Of Osteoblastsmentioning
confidence: 99%